2022
DOI: 10.1002/gamm.202200004
|View full text |Cite
|
Sign up to set email alerts
|

Active control of compressible channel flow up to Mab=3 using direct numerical simulations with spanwise velocity modulation at the walls

Abstract: Active turbulence control has been pursued continuously for the last decades, striving for an altered, energetically more favorable flow. In this article, our focus is on a promising method inducing a spanwise wall movement in order to reduce turbulence intensity and hence friction drag, investigated by means of direct numerical simulation. This approach transforms a previously time dependent oscillatory wall motion into a static spatial modulation with prescribed wavelength in the streamwise direction [48]. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…(1995) for the plane channel, and employed in all previous compressible studies of drag reduction by spanwise wall motion (Fang et al. 2009; Yao & Hussain 2019; Ruby & Foysi 2022). The ZBC simulations indicate that compressibility leads to a larger drag reduction achieved by spanwise forcing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1995) for the plane channel, and employed in all previous compressible studies of drag reduction by spanwise wall motion (Fang et al. 2009; Yao & Hussain 2019; Ruby & Foysi 2022). The ZBC simulations indicate that compressibility leads to a larger drag reduction achieved by spanwise forcing.…”
Section: Methodsmentioning
confidence: 99%
“…The few available compressible data are from Yao & Hussain (2019), who considered the oscillating wall only, at the slightly higher for and for . Moreover, the data points computed by Ruby & Foysi (2022) for a stationary wave are at and .…”
Section: Drag Reduction and Power Savingsmentioning
confidence: 99%
“…Ruby and Foysi [8] use DNS of compressible channel flows up to bulk Mach number Ma b = 3 to explore spanwise wall velocity modulation as a mechanism to actively control turbulence. Because of the strong fluctuations in viscosity, density and temperature within the near-wall region of the supersonic flow, the effect of the control method is substantially modified as compared to incompressible flow conditions [10].…”
Section: P R E F a C E Preface To Special Issue On Direct Numerical S...mentioning
confidence: 99%
“…The StTW, introduced by Quadrio, Ricco & Viotti (2009), are interesting owing mainly to their good energetic performance, which is preserved at high Reynolds numbers (Gatti & Quadrio 2016). The StTW are effective even in compressible and supersonic flows (Ruby & Foysi 2022;Gattere et al 2024), and have been demonstrated to affect favourably the aerodynamic drag of a three-dimensional body (Banchetti, Luchini & Quadrio 2020), up to the point that an actuation over a limited portion of the wing of an airplane in transonic flight reduces the total drag of the aircraft by nearly 10 % at a negligible energy cost (Quadrio et al 2022).…”
Section: Introductionmentioning
confidence: 99%